Quantum Chemical Exploration of Carbonofluoridic Acid's Structural, Electronic, and Spectroscopic Properties - Basnet, Khakendra; Neupane, Bhijan (Journal of Nepal Chemical Society, 2025)
The structural and electronic properties of the title molecule were investigated using Density Functional Theory (DFT) at the B3LYP/6-311G++(d,p) level in Gaussian G09 W and GaussView. Geometrical optimization was performed to determine the most stable configuration, with total energy computations revealing the minimized energy state. The electronic properties were analyzed through HOMO-LUMO gap calculations, yielding a band gap of 8.68708 eV, indicating high kinetic stability and low reactivity. Global reactivity indices, including electrophilicity, hardness, and electronegativity, were evaluated to ascertain the chemical behavior of the molecule. Molecular Electrostatic Potential (MEP) analysis identified reactive sites, with oxygen atoms showing a negative potential for electrophilic attack, while hydrogen atoms exhibited a positive potential, favoring nucleophilic interactions. Frontier molecular orbitals were further explored using the Total, Partial, and Overlap Density of States (TDOS, PDOS, and OPDOS) to elucidate the charge distribution and orbital contributions. Electron Localization Function (ELF) and Localized Orbital Locator (LOL) analyses revealed the electron density distribution, highlighting regions of strong covalent interactions and localized bonding characteristics. A Reduced Density Gradient (RDG) was employed to visualize non-covalent interactions, indicating van der Waals interactions and steric effects. Fukui functions and dual descriptors were calculated to predict reactive sites and charge-transfer tendencies. Spectroscopic characterization via FT-IR and FT-Raman spectroscopy confirmed the key functional group vibrations. These insights contribute to the understanding of the reactivity and stability of the title molecule and its potential applications in materials science and biochemistry.